Propuesta de mejora de la estrategia de mantenimiento para los motores de media y baja tensión, de la refinería de Cartagena (2020)
This work presents a proposal to update or improve the maintenance strategy for medium and low voltage electric motors of the company Ecopetrol S.A. taking into account the lower number of Man Hours programmed due to the shortage of own personnel, unnecessary tasks and real time in the execution of the failure mode. They are the designed proposal that seeks to apply the RCM methodology with good results that allows optimizing the information system and improving and facilitating maintenance tasks and ensuring that they are carried out in less time, thus reducing losses due to poor operation; being also a relief in the economy of the company. A descriptive approach investigation was developed, first identifying technical information about the company's electric motors and their maintenance plan, then a descriptive analysis of failures and criticality was carried out, identifying actions to detect critical equipment, in the In the exercise, a comparison was made of the work routes while the proposals for optimized routes were shown to finally present the proposal that optimizes the company's resources by reducing man hours.